PEMIKIRIAN PENDIDIKAN ISLAM PERSPEKTIF KH. ABDURRAHMAN WAHID - Adam, Mukhamad Fahmi; Munir, Miftahkhul; Umro, Jakaria (Tajdid: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2025)
Gus Dur's views on Islamic education are inseparable from his background as a santri (Islamic student), academic, and social and political observer. Amid the challenges of globalization and the tide of radicalism, Gus Dur's thoughts are relevant to further study as a basis for developing a moderate and contextual model of Islamic education. The method used is library research, where library research is a qualitative research method conducted with literature (libraries), in the form of books, notes, and research reports from previous studies. Islamic education seeks to provide assistance to free humans from the oppression that suffocates them. Truly liberating education can only be implemented by those who are able to overcome their naivety and have a commitment to truly liberate. This study aims to describe the concept of Islamic educational thought from the perspective of KH. Abdurrahman Wahid and analyze the relevance of KH. Abdurrahman Wahid's thoughts to education in Indonesia.